PERILAKU KOMUNITAS MUSLIM PERKOTAAN DALAM MENGONSUMSI PRODUK HALAL - Muchtar Muchtar (Harmoni, 2012)
For the Muslims consuming the allowed (halal Isl.) food and drink is an obligation, as consuming the food and drink that is not halal could have a negative impact on their health. In Indonesia, the Muslim consumers are protected by the government in this case is the National, Inspectional Agency of Drug and Food (BPOM) which oversees the product circulation in the society. Actually the consumption pattern of the Muslims has been set up in the teachings called syariat. In the teachings of syariat, it is not permissible for Muslims to consume certain products because they contain a substance or process which attached to them away from the teaching of syariat. Islamic syariat teaching is so firm that necessitates Muslims to avoid the things forbidden by Allah SWT and do whatever he was told. This makes the Muslim consumers from various segments, are not permissive consumers in the consumption behavior patterns. They are limited by the halal (allowed) and haram (forbidden) which is written in the Qur’an and AlHadith, main guides for them.